2023
DOI: 10.29333/ejmste/13111
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of using the model-based thinking strategy in developing first-grade high school students’ physical concepts and inquiry thinking skills

Abstract: This research aimed to verify the effectiveness of using the model-based thinking strategy in developing first-grade high school students’ physical concepts and inquiry thinking skills. To achieve this goal, the research used the experimental approach with a quasi- experimental design for the experimental and control groups. The sample of the study consisted of 67 students in the first grade of high school, and it was divided into two groups: the experimental group 33 students (who studied using the model-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…The sub‐skills found to promote conceptual change include hypothesis testing, control of variables, evaluation of evidence, and hypothetical‐deductive, probabilistic, and proportional reasoning (e.g., Lawson et al, 2000; Torres & Zeidler, 2002; Zimmerman, 2000). Some recent research has shown that student reasoning skills, especially evidence‐based reasoning, and control of variables, do seem to be affected by modeling‐based pedagogies or vice versa (Russ & Odden, 2017, Tolba & Al‐Osaimi, 2023; Wang et al, 2015). Interestingly, Russ and Odden (2017) discovered that in undergraduate physics classes the use of evidence‐based reasoning or the evaluation of evidence occurred simultaneously with model‐based reasoning when students worked on constructing static electricity models showing that they seemed to be intertwined.…”
Section: Theoretical and Empirical Perspectivesmentioning
confidence: 99%
“…The sub‐skills found to promote conceptual change include hypothesis testing, control of variables, evaluation of evidence, and hypothetical‐deductive, probabilistic, and proportional reasoning (e.g., Lawson et al, 2000; Torres & Zeidler, 2002; Zimmerman, 2000). Some recent research has shown that student reasoning skills, especially evidence‐based reasoning, and control of variables, do seem to be affected by modeling‐based pedagogies or vice versa (Russ & Odden, 2017, Tolba & Al‐Osaimi, 2023; Wang et al, 2015). Interestingly, Russ and Odden (2017) discovered that in undergraduate physics classes the use of evidence‐based reasoning or the evaluation of evidence occurred simultaneously with model‐based reasoning when students worked on constructing static electricity models showing that they seemed to be intertwined.…”
Section: Theoretical and Empirical Perspectivesmentioning
confidence: 99%
“…It promotes the development of critical thinking and argumentation skills, as well as the ability to apply the knowledge in practice (Amaliyah et al, 2023;Cahyarini et al, 2016;Chen, 2021;Chu et al, 2017;Ha et al, 2023;Miarti et al, 2021;Vafaeikia et al, 2023). It also facilitates the development of inquiry skills or scientific process skills (Cakir, 2017;Ergul, 2011;Harlen, 2021;Ješková et al, 2022;Liu et al, 2021;Ozkul & Ozden, 2020;Tolba & Al-Osaimi, 2023;Wale & Bishaw, 2020) such as formulation of research questions and hypotheses, provision of evidence, evaluation of explanations, and conclusion-drawing. Moreover, the 5E model promotes the development of scientific literacy (Areepattamannil et al, 2020;Bybee, 2019).…”
Section: Introductionmentioning
confidence: 99%